Iron-based sodium barium niobate ceramic material with high energy storage performance and preparation method of iron-based sodium barium niobate ceramic material

By performing iron ion replacement in barium niobate ceramics and using standard solid phase sintering, the problem of poor sintering performance of traditional barium niobate ceramics is solved, significantly improving the density and energy storage performance of the material, and achieving efficient energy storage density and breakdown field strength.

CN119638418AActive Publication Date: 2025-03-18NANJING XIAOZHUANG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411682685.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-18
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

Traditional barium niobate ceramics have poor sintering performance and are difficult to prepare. After sintering, the samples are difficult to obtain dense structures and are prone to cracks. Their breakdown strength is small and their energy storage density is low, making it difficult to meet the needs of modern industries.

Method used

By performing iron ion replacement in barium niobate sodium ceramic, the composition of Ba4-2xSm2xNa2FexNb10-xO30 is specifically adopted, where 1≤x≤1.25 is used to replace Ba2+ in position A and Fe3+ in position B, and sintering is carried out by standard solid phase method to obtain iron-based barium niobate sodium ceramic material with high energy storage performance.

Benefits of technology

The density of ceramic materials is significantly improved, pores and cracks are reduced, breakdown field strength, energy storage density and energy storage efficiency are improved, the maximum breakdown field strength reaches 510kV/cm, the energy storage density is 5.02J/cm3, and the energy storage efficiency is 74.5%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005148747070000061
    Figure BDA0005148747070000061
  • Figure BDA0005148747070000062
    Figure BDA0005148747070000062
  • Figure HDA0005148747080000011
    Figure HDA0005148747080000011
Patent Text Reader

Abstract

The invention discloses an iron-based sodium barium niobate ceramic material with high energy storage performance and a preparation method thereof, the composition of the iron-based sodium barium niobate ceramic material is Ba (4-2x) Sm (2x) Na2FexNb (10-x) O30, and x is greater than or equal to 1 and less than or equal to 1.25. Barium carbonate, samarium oxide, sodium carbonate, ferric oxide and niobium pentoxide are used as raw materials, and a standard solid-phase method is adopted for sintering to prepare the samarium-doped barium carbonate. According to the product formula, iron is selected to replace niobium in barium sodium niobate, the product is lead-free and environment-friendly, iron reserves are rich, the price is low, the cost of raw materials is favorably controlled, iron replacement is favorable for enhancing the relaxor ferroelectric property of the material, a slender ferroelectric hysteresis loop can be obtained, and the energy storage efficiency of the material is improved. The prepared ceramic material has the advantages of few pores and cracks, high density, obviously improved microstructure, finer and more uniform grain size, obviously improved ferroelectric polarization strength and obviously improved breakdown field strength, solves the problem that the barium sodium niobate material is difficult to sinter, and obviously improves the ferroelectric property and energy storage property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an iron-based sodium barium niobate ceramic material with high energy storage performance and a preparation method thereof, belonging to the technical field of ceramic materials. Background Art

[0002] With the development of pulse power technology, pulse power equipment energy storage components that can achieve instantaneous charging and discharging have been widely used in modern industrial fields such as electromagnetic railgun weapons, ship propulsion systems, defense, hybrid vehicles, geological exploration, and medical equipment. Dielectric ceramic capacitors have become one of the most widely used energy storage devices due to their ultra-high power density, good thermal stability, mechanical stability, and excellent high-voltage resistance.

[0003] Barium sodium niobate ceramics have high Curie temperature, moderate dielectric constant and ferroelectric polarization value, good temperature stability, and great application potential in the field of dielectric energy storage devices. However, traditional barium sodium niobate ceramics have poor sintering performance and are difficult to prepare. It is difficult to obtain a dense structure after sintering, and cracks are prone to occur. They have low breakdown strength and low energy storage density, which makes it difficult to meet the needs of modern industry. Modifying their sintering performance and energy storage performance is a major problem that needs to be solved urgently.

[0004] Ion substitution is an important way to improve the properties of sodium barium niobate ceramics. Jindal et al. found that Cu 2+ Ion substitution can effectively inhibit the abnormal grain growth in sodium barium niobate and reduce the residual polarization value (see S. Jindal, S. Devi, KM Batoo, G. Kumar, and A. Vasishth, Impact of copper substitution on the structural, ferroelectric and magnetic properties of tungsten bronze ceramics. Phys. B Condens. Matter, 2018, 537: 87-92); Run Li et al. found that Ca 2+ The replacement of can reduce the pores of ceramics and increase the polarization strength, resulting in a breakdown field strength of 120 kV / cm and a breakdown field strength of 0.83 J / cm 3 Energy storage density (see R.Li, YPPu, QWZhang, W.Wang, JWLi, XYDu, M.Chen, X.Zhang, and ZXSun, The relationship between enhanced dielectric property and structural distortion in Ca doped Ba2NaNb5O15 Tungsten bronze ceramics. J. Eur. Ceram. Soc., 2020, 40: 4509-4516). However, the sintering performance of most sodium barium niobate modified ceramics has not been significantly improved, the breakdown field strength of the material is lower than 150 kV / cm, and the energy storage density and energy storage efficiency are low, which is far from meeting the requirements, limiting its application in pulse power energy storage devices. Summary of the invention

[0005] Purpose of the invention: The first purpose of the present invention is to provide an iron-based sodium barium niobate ceramic material with high energy storage performance. The second purpose of the present invention is to provide a method for preparing the iron-based sodium barium niobate ceramic material with high energy storage performance.

[0006] Technical solution: The iron-based sodium barium niobate ceramic material with high energy storage performance described in the present invention is characterized in that the composition of the iron-based sodium barium niobate ceramic material is: Ba 4-2x Sm 2x Na2Fe x Nb 10-x O 30 , where 1≤x≤1.25, and x represents the amount of ion replacement.

[0007] Furthermore, the iron-based sodium barium niobate ceramic material with high energy storage performance is obtained by replacing the Nb at the B position in the sodium barium niobate crystal structure with 5+ With Fe 3+ Substitution, Ba at position A 2+ Use Sm 3+ replace.

[0008] Furthermore, the iron-based sodium barium niobate ceramic material with high energy storage performance has a breakdown field strength of 500-510 kV / cm and an energy storage density of 4.20-5.02 J / cm 3 , the energy storage efficiency is 68.9% to 74.5%.

[0009] The method for preparing the iron-based sodium barium niobate ceramic material with high energy storage performance of the present invention comprises the following steps:

[0010] (1) Barium carbonate, samarium oxide, sodium carbonate, iron trioxide, and niobium pentoxide are used as raw materials and the mixture is prepared according to the chemical formula Ba 4-2x Sm 2x Na2Fe x Nb 10-x O 30 Weighing and mixing, and pre-sintering to obtain ceramic powder;

[0011] (2) mixing ceramic powder with a binder, granulating, screening, and pressing to obtain a ceramic green body;

[0012] (3) Sintering the ceramic green body to obtain the high-performance iron-based sodium barium niobate ceramic material.

[0013] Furthermore, in step (1), the purity of the raw material powders of barium carbonate, samarium oxide, sodium carbonate, iron trioxide and niobium pentoxide is above 99%.

[0014] Furthermore, in step (1), the mixing method is ball milling, anhydrous ethanol and zirconium oxide balls are ball milling media, the ball milling speed is 100 to 130 rpm, and the mixing ball milling time is 4 to 6 hours.

[0015] Furthermore, in step (1), the pre-firing temperature is 1000-1200° C., and the pre-firing time is 2-4 hours.

[0016] Furthermore, in step (2), the binder is a polyvinyl alcohol aqueous solution with a concentration of 4 to 6 wt %, and the amount of the binder added is 5 to 7% of the volume of the ceramic powder, and the sieve is 40 mesh.

[0017] Furthermore, in step (2), the pressing pressure during the pressing process is 98 MPa, and the holding time after the pressing is completed is 3 to 5 minutes.

[0018] Furthermore, in step (3), the sintering temperature is 1175-1250° C., the heating rate is 5° C. / min, and the sintering time is 2-4 h.

[0019] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0020] (1) The product formula of the present invention selects iron to replace niobium in sodium barium niobate. Iron reserves are abundant and the price is low, which is conducive to controlling the cost of raw materials and is lead-free and environmentally friendly.

[0021] (2) The iron-based sodium barium niobate ceramic material prepared by the present invention has few pores and cracks and high density.

[0022] The sodium barium niobate ceramics sintered by the standard solid phase method are difficult to be dense and have many pores and cracks. However, after the iron ion is replaced by the standard solid phase method of the present invention, a dense ceramic material with few pores and cracks can be obtained.

[0023] (3) The microstructure of the iron-based sodium barium niobate ceramic material prepared by the present invention is significantly improved, the density is increased, the grain size is finer and more uniform, and the ferroelectric polarization strength and breakdown field strength are significantly improved (the maximum breakdown field strength is 510 kV / cm, and the energy storage density is 5.02 J / cm 3, the energy storage efficiency is 74.5%). At the same time, iron substitution is conducive to enhancing the relaxor ferroelectric properties of the material and obtaining a more slender hysteresis loop, thereby improving the energy storage efficiency of the material.

[0024] (4) The present invention solves the problem that sodium barium niobate-based materials are difficult to sinter, and at the same time significantly improves the ferroelectric properties and energy storage properties of the system materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 XRD patterns of ceramic materials obtained for Examples 1-2 and Comparative Examples 1-3;

[0026] Figure 2 Microscopic morphology of ceramic materials obtained for Examples 1-2 and Comparative Examples 1-3;

[0027] Figure 3 The unipolar hysteresis loop diagram of the ceramic material obtained in Example 1;

[0028] Figure 4 The unipolar hysteresis loop diagram of the ceramic material obtained in Example 2 is

[0029] Figure 5 The unipolar hysteresis loop diagrams of the ceramic materials obtained for Comparative Examples 1-3. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0031] Example 1Ba 4-2x Sm 2x Na2Fe x Nb 10-x O 30 , x = 1, namely Ba2Sm2Na2FeNb9O 30 Preparation

[0032] According to the chemical reaction formula, the amount of raw materials required for this experiment is accurately calculated according to the stoichiometric ratio. The raw materials are: barium carbonate (purity 99.95%), samarium oxide (purity 99.99%), sodium carbonate (purity 99.99%), ferric oxide (purity 99.9%), and niobium pentoxide (purity 99.9%). Use a high-precision electronic balance to weigh and ensure that the weighing accuracy is 0.001g. Put the above-prepared powder into an alumina ball mill. The ball milling medium is selected from small-sized zirconium oxide balls and anhydrous ethanol solution. The amount of anhydrous ethanol added does not exceed 1 / 2 of the alumina ball mill body. Put the ball mill with the sample into a planetary ball mill for ball milling at a speed of 130 rpm for 6 hours to obtain a slurry. Pour the mixed slurry into a clean enamel tray and dry at room temperature. After drying, pass through a 120-mesh sieve, place it in a muffle furnace and pre-sinter it at 1100°C for 3 hours to obtain the required powder. The pre-sintered powder is placed in a ball mill for secondary ball milling. The ball milling conditions are the same as the first time. After ball milling, the powder is poured out and dried naturally at room temperature. After drying, it is sieved through a 120-mesh sieve. The sieved powder is placed in a mortar, and a polyvinyl alcohol aqueous solution (concentration of 6wt%) with a volume of 6% of the volume of the ceramic powder is added to mix evenly, and fully ground. After grinding, it is sieved with a 40-mesh sieve. Weigh an appropriate amount of powder and pour it into the mold. Press it. The pressure is 98MPa. After the pressure is completed, keep the pressure for 3-4 minutes. Press and preform to obtain a ceramic green cylindrical sheet with a diameter of 10mm and a thickness of about 2-3mm. The pressed ceramic green cylindrical sheet is placed in a muffle furnace and sintered in an atmospheric atmosphere. The sintering temperature is 1250℃, the heating rate is 5℃ / min, the sintering time is 3h, and the ceramic sample is taken out after naturally cooling to room temperature to obtain the iron-based sodium barium niobate ceramic material Ba2Sm2Na2FeNb9O 30 .

[0033] The prepared iron-based sodium barium niobate ceramic material Ba2Sm2Na2FeNb9O 30 X-ray diffraction analysis test was performed, and the results were as follows Figure 1 Attached Figure 1 Example 1 shows that Ba2Sm2Na2FeNb9O 30 X-ray diffraction pattern of .

[0034] Iron-based sodium barium niobate ceramic material Ba2Sm2Na2FeNb9O 30 After the surface was polished, it was hot-etched at 1125℃ for 30min. The samples were analyzed by scanning electron microscope. The results are as follows: Figure 2 Attached Figure 2 Example 1 shows that Ba2Sm2Na2FeNb9O 30 Surface morphology diagram.

[0035] Iron-based sodium barium niobate ceramic material Ba2Sm2Na2FeNb9O 30 Both sides were ground flat and thinned to about 0.15 mm. The electrodes were gold plated and the ferroelectric and energy storage properties were tested. The results are as follows: Figure 3 Attached Figure 3 Example 1 shows that Ba2Sm2Na2FeNb9O 30 hysteresis loop.

[0036] Example 2Ba 4-2x Sm 2x Na2Fe x Nb 10-x O 30 , x=1.25, that is, Ba 1.5 Sm 2.5 Na2Fe 1.25 Nb 8.75 O 30 Preparation

[0037] The preparation process is the same as that of Example 1, except that the value of x in the ingredients is different from that in Example 1, namely barium carbonate (purity 99.95%), samarium oxide (purity 99.99%), sodium carbonate (purity 99.99%), ferric oxide (purity 99.9%), and niobium pentoxide (purity 99.9%), and the sintering temperature of the ceramic green cylindrical sheet is 1175° C., and the other steps are the same as those of Example 1 to obtain an iron-based sodium barium niobate ceramic material Ba 1.5 Sm 2.5 Na2Fe 1.25 Nb 8.75 O 30 .

[0038] The prepared iron-based sodium barium niobate ceramic material Ba 1.5 Sm 2.5 Na2Fe 1.25 Nb 8.75 O 30 X-ray diffraction analysis test was performed, and the results were as follows Figure 1 As shown, attached Figure 1 Example 2 shows that Ba 1.5 Sm 2.5 Na2Fe 1.25 Nb 8.75 O 30 X-ray diffraction pattern of .

[0039] The iron-based sodium barium niobate ceramic material Ba 1.5 Sm 2.5 Na2Fe 1.25 Nb 8.75 O 30After the surface was polished, it was hot-etched at 1090℃ for 30min. The samples were analyzed by scanning electron microscope. The results are as follows: Figure 2 As shown, attached Figure 2 Example 2 shows that Ba 1.5 Sm 2.5 Na2Fe 1.25 Nb 8.75 O 30 Surface morphology diagram.

[0040] The iron-based sodium barium niobate ceramic material Ba 1.5 Sm 2.5 Na2Fe 1.25 Nb 8.75 O 300 Both sides were ground flat and thinned to about 0.15 mm. The electrodes were gold plated and the ferroelectric and energy storage properties were tested. The results are as follows: Figure 4 As shown, attached Figure 4 Example 2 shows that Ba 1.5 Sm 2.5 Na2Fe 1.25 Nb 8.75 O 30 hysteresis loop.

[0041] Comparative Example 1Ba 4-2x Sm 2x Na2Fe x Nb 10-x O 30 , x=0, namely Ba2NaNb5O 15 Preparation

[0042] The preparation process is the same as that of Example 1, except that x=0 during the batching process. Except that the value of x during the batching process is different from that of Example 1, and the sintering temperature of the ceramic green cylindrical sheet is 1300°C, the other steps are the same as those of Example 1 to obtain Ba2NaNb5O 15 .

[0043] The ceramic material Ba2NaNb5O 15 X-ray diffraction analysis test was performed, and the results were as follows Figure 1 As shown, attached Figure 1 Comparative Example 1 shows that Ba2NaNb5O 15 X-ray diffraction pattern of .

[0044] The ceramic material Ba2NaNb5O 15 After the surface was polished, it was hot-etched at 1125℃ for 30min. The samples were analyzed by scanning electron microscope. The results are as follows: Figure 2 As shown, attached Figure 2 Comparative Example 1 shows that Ba2NaNb5O 15 Surface morphology diagram.

[0045] The ceramic material Ba2NaNb5O 15 Both sides were ground flat and thinned to about 0.15 mm. The electrodes were gold plated and the ferroelectric and energy storage properties were tested. The results are as follows: Figure 5 As shown, attached Figure 5 Comparative Example 1 shows that Ba2NaNb5O 15 hysteresis loop.

[0046] Comparative Example 2Ba 4-2x Sm 2x Na2Fe x Nb 10-x O 30 , x=0.3, that is, Ba 3.4 Sm 0.6 Na2Fe 0.3 Nb 9.7 O 30 Preparation

[0047] The preparation process is the same as that of Example 1, except that x=0.3 during the batching process. Except that the value of x during the batching process is different from that of Example 1, and the sintering temperature of the ceramic cylindrical sheet green body is 1275°C, the other steps are the same as those of Example 1 to obtain a ceramic material Ba 3.4 Sm 0.6 Na2Fe 0.3 Nb 9.7 O 30 .

[0048] The ceramic material Ba 3.4 Sm 0.6 Na2Fe 0.3 Nb 9.7 O 30 X-ray diffraction analysis test was performed, and the results were as follows Figure 1 As shown, attached Figure 1 Comparative Example 2 shows that Ba 3.4 Sm 0.6 Na2Fe 0.3 Nb 9.7 O 30 X-ray diffraction pattern of .

[0049] The ceramic material Ba 3.4 Sm 0.6 Na2Fe 0.3 Nb 9.7 O 30 After the surface was polished, it was hot-etched at 1150℃ for 30min. The samples were analyzed by scanning electron microscope. The results are as follows: Figure 2 As shown, attached Figure 2 Comparative Example 2Ba is shown 3.4 Sm 0.6 Na2Fe0.3 Nb 9.7 O 30 Surface morphology diagram.

[0050] The ceramic material Ba 3.4 Sm 0.6 Na2Fe 0.3 Nb 9.7 O 30 Both sides were ground flat and thinned to about 0.15 mm. The electrodes were gold plated and the ferroelectric and energy storage properties were tested. The results are as follows: Figure 5 As shown, attached Figure 5 Comparative Example 2 shows that Ba 3.4 Sm 0.6 Na2Fe 0.3 Nb 9.7 O 30 hysteresis loop.

[0051] Comparative Example 3Ba 4-2x Sm 2x Na2Fe x Nb 10-x O 30 , x = 0.5, namely Ba3SmNa2Fe 0.5 Nb 9.5 O 30 Preparation

[0052] The preparation process is the same as that in Example 1, except that x=0.5 during the batching process. In addition to the different value of x during the batching process and the sintering temperature of the ceramic green cylindrical sheet being 1250°C, the other steps are the same as those in Example 1 to obtain the ceramic material Ba3SmNa2Fe 0.5 Nb 9.5 O 30 .

[0053] The ceramic material Ba3SmNa2Fe 0.5 Nb 9.5 O 30 X-ray diffraction analysis test was performed, and the results were as follows Figure 1 Attached Figure 1 Comparative Example 3 shows that Ba3SmNa2Fe 0.5 Nb 9.5 O 30 X-ray diffraction pattern of .

[0054] The ceramic material Ba3SmNa2Fe 0.5 Nb 9.5 O 30 After the surface was polished, it was hot-etched at 1125℃ for 30min. After hot-etching, the sample was analyzed by scanning electron microscope. The results are as follows: Figure 2 As shown, attached Figure 2Comparative Example 3 shows that Ba3SmNa2Fe 0.5 Nb 9.5 O 30 Surface morphology diagram.

[0055] The ceramic material Ba3SmNa2Fe 0.5 Nb 9.5 O 30 Both sides were ground flat and thinned to about 0.15 mm. The electrodes were gold plated and the ferroelectric and energy storage properties were tested. The results are as follows: Figure 5 As shown, attached Figure 5 Comparative Example 3 shows that Ba3SmNa2Fe 0.5 Nb 9.5 O 30 hysteresis loop.

[0056] Figure 1 The XRD patterns of the ceramic materials obtained for Examples 1-2 and Comparative Examples 1-3 are as follows: Figure 1 It can be seen that comparative examples 1, 2, and 3 are pure phases with tetragonal tungsten bronze structures, while the main phases of examples 1 and 2 are tetragonal tungsten bronze structures, and also contain a small amount of ferric oxide as a second phase. The PDF cards corresponding to the comparative examples and examples are 40-1463 and 39-0265.

[0057] Figure 2 The microscopic morphology of the ceramic material obtained for Examples 1-2 and Comparative Examples 1-3, wherein (a) is Comparative Example 1, (b) is Comparative Example 2, (c) is Comparative Example 3, (d) is Example 1, and (e) is Example 2. Figure 2 It can be seen that with the increase of iron content, cracks and pores are significantly reduced, density is significantly increased, and grain size is more uniform.

[0058] Compared with Comparative Examples 1, 2 and 3, the grain sizes of Examples 1 and 2 are finer.

[0059] Figure 3 The unipolar hysteresis loop diagram of the ceramic material obtained in Example 1 is: Figure 4 The unipolar hysteresis loop diagram of the ceramic material obtained in Example 2 is: Figure 5 The unipolar hysteresis loop diagram of the ceramic material obtained for Comparative Examples 1-3 is shown in FIG. Figure 3-5 It can be seen that the maximum polarization value of Examples 1 and 2 is larger, reaching 22.2 μC / cm 2 and 19.5μC / cm 2 , while the ceramic material planning values ​​obtained in Comparative Examples 1-3 are all 15μC / cm 2 the following.

[0060] according to Figure 3-5The unipolar hysteresis loop diagram shown in the figure can be used to obtain the breakdown field strength of each embodiment and comparative example and calculate its total energy storage density, effective energy storage density and energy storage efficiency. The calculation formula is:

[0061]

[0062] Among them, W total , W rec and η are the total energy storage density, effective energy storage density and energy storage efficiency, respectively. E, P, P max and P r are the applied electric field, polarization value, maximum polarization value and remanent polarization value, respectively.

[0063] The performance parameters of the ceramic materials obtained in Examples 1-2 and Comparative Examples 1-3 are shown in Table 1.

[0064] Table 1 Composition and energy storage performance parameters of ceramic materials

[0065]

[0066] As can be seen from Table 1, with the increase of iron content, the relaxor ferroelectricity of the material is enhanced, the hysteresis loop is more slender, and the energy storage efficiency is higher. The breakdown field strength of Examples 1 and 2 is higher, which is 510 kV / cm and 500 kV / cm respectively, and the energy storage density is higher, which is 5.02 J / cm 3 , 4.20J / cm 3 , the energy storage efficiency of Example 1 and Example 2 are 74.5% and 68.9% respectively. Therefore, when the iron content increases, the energy storage performance of the material improves. When the addition amount reaches x=1, the energy storage performance reaches the optimal value. When the iron content is further increased, the energy storage performance decreases again. Compared with Comparative Example 1 without iron addition and Comparative Examples 2 and 3 with less iron addition, the appropriate amount of iron addition such as Example 1 has high energy storage performance, indicating that increasing iron can enhance the energy storage performance of the material.

Claims

1. An iron-based sodium barium niobate ceramic material with high energy storage performance, characterized in that: The composition of the iron-based sodium barium niobate ceramic material is: Ba 4-2x Sm 2x Na2Fe x Nb 10-x O 30 , where 1≤x≤1.

25.

2. The iron-based sodium barium niobate ceramic material with high energy storage performance according to claim 1, characterized in that: The iron-based sodium barium niobate ceramic material with high energy storage performance is obtained by replacing the Nb at the B position in the sodium barium niobate crystal structure with 5+ With Fe 3+ Substitution, Ba at position A 2+ Use Sm 3+ replace.

3. The method for preparing the iron-based sodium barium niobate ceramic material with high energy storage performance according to claim 1 or 2, characterized in that: The following steps are involved: (1) Barium carbonate, samarium oxide, sodium carbonate, iron trioxide, and niobium pentoxide are used as raw materials and the mixture is prepared according to the chemical formula Ba 4- 2x Sm 2x Na2Fe x Nb 10-x O 30 Weighing and mixing, and pre-sintering to obtain ceramic powder; (2) mixing ceramic powder with a binder, granulating, screening, and pressing to obtain a ceramic green body; (3) Sintering the ceramic green body to obtain the high-performance iron-based sodium barium niobate ceramic material.

4. The preparation method according to claim 3, characterized in that: In step (1), the purity of the raw material powders of barium carbonate, samarium oxide, sodium carbonate, iron trioxide and niobium pentoxide is above 99%.

5. The preparation method according to claim 3, characterized in that: In step (1), the mixing method is ball milling, anhydrous ethanol and zirconium oxide balls are ball milling media, the ball milling speed is 100 to 130 revolutions per minute, and the mixing ball milling time is 4 to 6 hours.

6. The preparation method according to claim 3, characterized in that: In step (1), the pre-firing temperature is 1000-1200° C., and the pre-firing time is 2-4 hours.

7. The preparation method according to claim 3, characterized in that: In step (2), the binder is a polyvinyl alcohol aqueous solution with a concentration of 4 to 6 wt %. The amount of the binder added is 5 to 7 % of the volume of the ceramic powder, and the sieve is 40 mesh.

8. The preparation method according to claim 3, characterized in that: In step (2), the pressing pressure during the pressing process is 98 MPa, and the holding time after the pressing is completed is 3 to 5 minutes.

9. The preparation method according to claim 3, characterized in that: In step (3), the sintering temperature is 1175-1250° C., the heating rate is 5° C. / min, and the sintering time is 2-4 h.

Citation Information

Patent Citations

  • Full-filled tungsten bronze structure high-entropy ferroelectric ceramic material and preparation method thereof

    CN115180944A

  • Ceramic capacitor dielectric material for energy storage and preparation method and application thereof

    CN117410098A

  • Preparation method of barium sodium niobate cylindrical monocrystal particle

    CN1493718A

  • Sealing Equipment for Waste Synthetic Resin Pyrolysis System

    KR102660635B1

  • Method for preparing nanotubes of piezoelectric material and nanotubes of piezoelectric material obtained thereby

    US20100102033A1